Mechanisms underlying HIV-1 Vpu-mediated viral egress - Roy, Nicolas; Pacini, Grégory; Berlioz-Torrent, Clarisse; Janvier, Katy (Frontiers in Microbiology, 2014)
Viruses such as lentiviruses that are responsible for long lasting infections, have to evade several level of cellular immune mechanisms to persist and efficiently disseminate in the host. Over the past decades, many evidences have emerged regarding the major role of accessory proteins of primate lentiviruses (Human (HIV) and simian immunodeficiency viruses (SIV)) in viral evasion from the host immune defense. This short review will provide an overview of the mechanism whereby the accessory protein Vpu contributes to this escape. Vpu is a multifunctional protein that was shown to contribute to viral egress by down-regulating several mediators of the immune system such as CD4, CD1d, NTB-A and the restriction factor BST2. The mechanisms underlying its activity are not fully characterized but rely on its ability to interfere with the host machinery regulating proteins turnover and vesicular trafficking. This review will focus on our current understanding of the mechanisms whereby Vpu down-regulates CD4 and BST2 expression level to favour viral egress.